Uji Empirik Crowding Out Surat Utang Pemerintah dan Korporasi di Pasar Modal Indonesia - Wibowo, Buddi; Passagi, Hendrikus; Prasetyo, Muhammad Budi (Jurnal Ekonomi Kuantitatif Terapan, 2018)
Financing government budget deficit through emission of government  bonds may create a crowding out in corporate bond market. Crowding out caused the cost of funds incurred by the corporation to be expensive so the corporate bond market is stagnant and banks become the only major source of funding. Sources of funding that are so dependent on the banking sector could threaten financial stability and the country's economy as a whole because of the banks’ systemic risk. Default of a bank not only can influence other banks but also can have a serious impact on the national economy. This research empirically examine the phenomenon of crowding out in Indonesia with a fixed effect model of panel data FGLS and show existence of crowding out, where the yield spread tends to rise when the government issued new debt securities. But the rise in the yield spread was more due to the increase in Credit Default Swaps (CDS) spreads which reflect the default risk of Indonesia, as well as showing the influence of foreign investors in the Indonesian capital market which is strongly influenced by  CDS.